Estudo dos efeitos de processamento sobre o comportamento estrutural e magnético do composto intermetálico La(Fe1-xSix)13 - Pierre-louis de Assis (2007)
In the present work we conduct an analysis of the relations between the crystal structure, chemical composition and magnetic behavior in intermetallic compounds of the La(Fe1-xSix)13 family in the range 0,11 < x < 0,14 and how they are affected by sintering. We show that the nominal stoichiometry does not correspond to that observed in the intermetallic phase when á-Fe is simultaneously formed . We also correlate theeffects of sintering to the magnetic behavior of the material by altering its transition temperature and possibly its magnetocaloric effect. Possible mechanisms for this are discussed in terms of the present knowledge regarding the origins of the magnetocaloric effect in La(Fe1-xSix)13 compounds.